2014
DOI: 10.13092/lo.59.1141
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of Man's Behavioral and Physical Characteristics as Animal Metaphors in the Spoken Discourse of Khezel People

Abstract: Cognitive theory of metaphor has changed our understanding of metaphor as a figurative device to a matter of thought. It holds that metaphors are cognitively as well as culturally motivated. Despite having similar images in some languages, the culture-specific aspect of animal metaphors inspired the researchers to explore this area of metaphoric system in a local Kurdish variety to investigate how animal metaphors are reflected in spoken discourse. To achieve this objective, the authors collected and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…People's perceptions also played a role in each connotation. According to Aliakbari and Faraji (2013), animal expressions can reveal individual or social thoughts. The findings also revealed that animal names in the Algerian society are more degrading than praising, and are used to describe aspects of appearance, size, physical characteristics, and behavioral characteristics by transferring animal features to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People's perceptions also played a role in each connotation. According to Aliakbari and Faraji (2013), animal expressions can reveal individual or social thoughts. The findings also revealed that animal names in the Algerian society are more degrading than praising, and are used to describe aspects of appearance, size, physical characteristics, and behavioral characteristics by transferring animal features to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, animal expressions serve as a reflection of individuals' and society's beliefs, cultural backgrounds, social behaviors, and roles. Aliakbari and Faraji (2013) conducted research on the metaphorical system of a local Kurdish dialect, focusing on the use of animal metaphors in order to explore their cultural significance in spoken discourse. Their approach involved collecting and analyzing animal expressions used to praise and degrade physical and behavioral characteristics in the Khezeli dialect of Ilam, Iran, over a period of three years.…”
Section: Literature Reviewmentioning
confidence: 99%